Meningkatkan Kemampuan Berpikir Kritis Hasil Belajar Materi Siklus Air Menggunakan Kombinasi Model PBL, TPACK & VIDEO - Febriyanti, Ervina; Radiansyah (CV. ITTC INDONESIA, 2023)
The concern addressed in this research pertains to the reduced activity levels, lack of critical thinking abilities and poor learning outcomes of fifth graders at SDN Kelayan Selatan 6 Banjarmasin, which are brought on by learning that only occurs in one direction, teaching that only employs lectures, students who are not faced with challenges and learning that does not employ the proper strategy. This study’s objective is to describe teacher actions and assess student activities, critical thinking abilities and learning outcomes in instruction utilizing the PBL model paired with the TPACK method based on instructional video medium. This study used a three meeting Classroom Action Research (CAR) technique that combines a qualitative and quantitative methodology. The outcomes of study utilizing this approach are as follows: student engagement at meeting 1 meets the requirement for being active with a percentage of 73% and at meeting 3 it climbs to satisfy the criteria for being highly active with a percentage of 93%. At meeting 1, students critical thinking abilities scored in the less critical group with a percentage of 13% and at meeting 3, they rose to the highly critical category with a percentage of 87%. Student learning outcomes in meeting 1 did not reach a value of 70 by getting 20% of students to finish, but at meeting 3, they were able to get 80% of students to finish, resulting in a value of 70.